Peran Pengetahuan Dan Sikap Remaja Putri Dilihat Dalam Tindakan Sadari (Periksa Payudara Sendiri) Dapat Menilai Deteksi Dini Kanker Payudara SMA Kartika 1-5 Padang Tahun 2024 - Eka Seba Marta; Reni Trevia (Jurnal Amanah Kesehatan, 2025)
West Sumatra has a cancer incidence rate (5.6%) higher than the national average (4.3%), which is the sixth highest out of 33 provinces in Indonesia. The purpose of this study is to see the Relationship between Knowledge and Attitude with BSE Actions as Early Detection of Breast Cancer in Grade X Female Students of SMA Kartika 1-5 Padang in 2024. This type of analytical research with a Cross-sectional design. The population was 189 people and the sample was taken using a simple random sampling technique, namely 65 people. This study was conducted in November-December 2024. Based on the results of the study, it was concluded that female students who did not perform BSE actions as early detection of breast cancer were female students who had low knowledge and negative attitudes towards breast cancer prevention measures. For this reason, respondents are expected to pay more attention to their breast condition by seeking information and knowledge about BSE actions as early detection of breast cancer.